2021
DOI: 10.3847/1538-3881/ac1f8e
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Exoplanetary Atmospheres at High Resolution with SPIRou: Detection of Water on HD 189733 b

Abstract: We present the first exoplanet atmospheric detection made as part of the SPIRou Legacy Survey, a Large Observing Program of 300 nights exploiting the capabilities of SPIRou, the new near-infrared high-resolution (R ∼ 70,000) spectropolarimeter installed on the Canada–France–Hawaii Telescope (3.6 m). We observed two transits of HD 189733b, an extensively studied hot Jupiter that is known to show prominent water vapor absorption in its transmission spectrum. When combining the two transits, we successfully detec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 101 publications
3
27
1
1
Order By: Relevance
“…HRCCS was developed in the near infrared, in order to study exoplanets in transmission and thermal emission (e.g. Snellen et al 2010;Brogi et al 2012Brogi et al , 2016Birkby et al 2013Birkby et al , 2017Casasayas-Barris et al 2019;Webb et al 2020;Boucher et al 2021), and it has only recently been applied in the optical for ultra-hot Jupiters such as Kelt-9 b (e.g. Yan & Henning 2018;Hoeijmakers et al 2018bHoeijmakers et al , 2019Pino et al 2020) and Wasp-76 b (e.g.…”
Section: Adaptations For Reflection Hrccsmentioning
confidence: 99%
“…HRCCS was developed in the near infrared, in order to study exoplanets in transmission and thermal emission (e.g. Snellen et al 2010;Brogi et al 2012Brogi et al , 2016Birkby et al 2013Birkby et al , 2017Casasayas-Barris et al 2019;Webb et al 2020;Boucher et al 2021), and it has only recently been applied in the optical for ultra-hot Jupiters such as Kelt-9 b (e.g. Yan & Henning 2018;Hoeijmakers et al 2018bHoeijmakers et al , 2019Pino et al 2020) and Wasp-76 b (e.g.…”
Section: Adaptations For Reflection Hrccsmentioning
confidence: 99%
“…Published low resolution studies of hot Jupiter atmospheres have reported tentative evidence for subsolar H 2 O abundances (Barstow et al 2017;Pinhas et al 2019;Welbanks et al 2019). This result was recently confirmed by high resolution spectroscopy of several planets, which show that subsolar H 2 O is often accompanied with supersolar CO abundances (Giacobbe et al 2021 Boucher et al 2021). Consequently, the measured C/O ratios of these planetary atmospheres are very high (0.85 − 1).…”
Section: The Origin Of Water-poor Hot Jupitersmentioning
confidence: 80%
“…Brogi et al (2018) presented the first detection of CO+H 2 O with TNG/GIANO, while Alonso-Floriano et al (2019) found water in the J and Y bands of CAHA/CARMENES. In 2021, CHFT/SPIRou also presented detections of H 2 O (Boucher et al 2021) and CO (Pelletier et al 2021). In the meantime, Giacobbe et al (2021) presented the si- Notes.…”
Section: Introductionmentioning
confidence: 98%